Sara's face - Burgess, Melvin (London Penguin Books, 2008)
Seventeen-year-old Sara wants so much to be famous that when a legendary, plastic-surgery-addicted rock star offers to take her under his wing and pay for her to have surgery too, she jumps at the chance despite her misgivings
1
Keywords: Emotional problems -- Fiction; Emotional problems of teenagers -- Juvenile fiction; Face -- Fiction; Face -- Juvenile fiction; Fame -- Juvenile fiction; Identity -- Fiction; Identity (Psychology) -- Juvenile fiction; Surgery, Plastic -- Juvenile fiction; Fame -- Fiction; Surgery, Plastic -- Fiction; England -- Juvenile fiction; England -- Fiction